Effectiveness Of Problem Based Learning (PBL) Model Based On Electric Circuit Study (ECS) On Dynamic Electricity Material Towards High School Student Creativity - Alberto Dio Nainggolan; Ady Frenly Simannulang; Sudirman T.P Lumbangaol (Jurnal Pendidikan, Sains Sosial, dan Agama, 2025)
This study aims to determine: The Effectiveness of the Problem Based Learning (PBL) Model Based on Electric Circuit Study (ECS) on Dynamic Electricity Material on the Creativity of Students of SMA Negeri 1 Siantar. This study design uses a Two Group pretest-posttest design, where the subject is given a pretest, followed by treatment (the use of the ECS virtual laboratory), and then given a posttest. The population of this study is all grade XII of SMA Negeri 1 Siantar, the sampling technique is purposive sampling of class XII-1 as the control class and class XII-2 as the experimental class. The dependent variable is the Effectiveness of the Problem Based Learning (PBL) Model Based on Electric Circuit Study (ECS) and the final variable is Student Creativity. The data collection technique uses a test instrument, the test instrument used is an essay test. The research data were analyzed using an Independent Sample T-test. The results of the Independent Sample T-test <0.05 which stated that the hypothesis was accepted. So it can be concluded that the Problem Based Learning (PBL) learning model based on Electric Circuit Study (ECS) is effective in increasing student creativity